2020
DOI: 10.1186/s13046-020-01693-w
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibitors: a novel strategy for tumor radiosensitization

Abstract: Recently, the focus of enhancing tumor radiosensitivity has shifted from chemotherapeutics to targeted therapies. Cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors are a novel class of selective cell cycle therapeutics that target the cyclin D-CDK4/6 complex and induce G1 phase arrest. These agents have demonstrated favorable effects when used as monotherapy or combined with endocrine therapy and targeted inhibitors, stimulating further explorations of other combination strategies. Multiple preclinical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 89 publications
(187 reference statements)
3
32
0
Order By: Relevance
“…Multiple preclinical and small sample clinical studies showed that CDK4/6 inhibitors exhibit a collaborative effect during radiotherapy in vitro and in vivo and show well-tolerated toxicity and promising efficacy in patients (44)(45)(46)(47). The potential mechanisms of clinical radiosensitization effects might be apoptosis enhancement, cell cycle progression blockage, and induction of cellular senescence and antitumor immunity (48). A preclinical study showed that abemaciclib and ionizing radiation (IR) had a good radiosensitization effect on tumor cells in proliferative and plateau-phase and tumor xenografts, but had little radiosensitization effect on normal cells, and improve the radiation sensitivity of NSCLC in vitro and in vivo.…”
Section: Cdk4/6 Inhibitors As Radiosensitizersmentioning
confidence: 99%
“…Multiple preclinical and small sample clinical studies showed that CDK4/6 inhibitors exhibit a collaborative effect during radiotherapy in vitro and in vivo and show well-tolerated toxicity and promising efficacy in patients (44)(45)(46)(47). The potential mechanisms of clinical radiosensitization effects might be apoptosis enhancement, cell cycle progression blockage, and induction of cellular senescence and antitumor immunity (48). A preclinical study showed that abemaciclib and ionizing radiation (IR) had a good radiosensitization effect on tumor cells in proliferative and plateau-phase and tumor xenografts, but had little radiosensitization effect on normal cells, and improve the radiation sensitivity of NSCLC in vitro and in vivo.…”
Section: Cdk4/6 Inhibitors As Radiosensitizersmentioning
confidence: 99%
“…The combination of CDK4/6i and RT has been considered of risk as it may exacerbate known CDK4/6i toxicities, particularly neutropenia and leukopenia. However, preclinical data indicate that CDK4/6i may enhance the therapeutic effects of RT [54,55].…”
Section: Radiotherapy and Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…The combination of CDK4/6i and RT has been considered of risk as it may exacerbate known CDK4/6i toxicities, particularly neutropenia and leukopenia. However, pre-clinical data indicate that CDK4/6i may enhance the therapeutic effects of RT [ 54 , 55 ]. Specifically, palbociclib may act as an inhibitor of double-stranded DNA repair [ 56 ], and abemaciclib as a multi-functional radiation modifier [ 57 ].…”
Section: Radiotherapy and Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…For the doseeffect-based median-effect principle, a CI<0.7 indicates synergism, a 0.7<CI>1.45 indicates an additive effect, while a CI>1. 45 indicates an antagonistic effect. The WST-1 assays were also complemented with assessment of cell confluence, cytotoxicity, and apoptosis using the IncuCyte S3 Live−Cell Analysis System, and the data extrapolated from these assays are presented below.…”
Section: Viabilitymentioning
confidence: 99%